2021
DOI: 10.1186/s12885-021-08938-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the analgesic effect of ultrasound-guided paravertebral block and ultrasound-guided retrolaminar block in Uniportal video-assisted Thoracoscopic surgery: a prospective, randomized study

Abstract: Background The optimal modality for postoperative analgesia after uniportal video-assisted thoracoscopic surgery (UVATS) for the treatment of lung cancer has not yet been determined. Both ultrasound-guided paravertebral block (PVB) and retrolaminar block (RLB) have been reported to be successful in providing analgesia after UVATS. However, which block technique provides superior analgesia after UVATS is still unclear. This randomized study was designed to compare the postoperative analgesic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Zhao et al [ 22 ] found that the analgesic effects of TRLB were superior to those of erector spinae blocks in patients with multiple rib fractures. Wang et al [ 9 ] compared ultrasound-guided TRLBs and paravertebral blocks for postoperative analgesia in patients undergoing video-assisted thoracoscopic surgery and found that the paravertebral block resulted in better analgesia than the TRLB. In contrast, Hwang et al [ 23 ] conducted a randomized placebo study that aimed to assess the analgesic efficacy of a single injection of ultrasound-guided TRLB after breast surgery and reported that TRLB did not reduce postoperative analgesic consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al [ 22 ] found that the analgesic effects of TRLB were superior to those of erector spinae blocks in patients with multiple rib fractures. Wang et al [ 9 ] compared ultrasound-guided TRLBs and paravertebral blocks for postoperative analgesia in patients undergoing video-assisted thoracoscopic surgery and found that the paravertebral block resulted in better analgesia than the TRLB. In contrast, Hwang et al [ 23 ] conducted a randomized placebo study that aimed to assess the analgesic efficacy of a single injection of ultrasound-guided TRLB after breast surgery and reported that TRLB did not reduce postoperative analgesic consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided thoracic retrolaminar block (TRLB) is a relatively new regional analgesic block that can be used as an alternative to the thoracic paravertebral block as a component of multimodal analgesia to control postoperative pain [ 5 ]. In adults, the analgesic efficacy of TRLB has been reported for rib fractures [ 6 ], breast surgery [ 7 , 8 ], and video-assisted thoracoscopic surgery [ 9 ]. Injecting a local anesthetic in the retrolaminar space blocks the ventral and dorsal rami of the thoracic spinal nerves and spreads laterally in the fascial plane to block the lateral cutaneous branch of the intercostal nerve and the small branches arising from it [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The length and number of incisions are less than that of the conventional approach of VATS. Therefore, anatomical structures such as muscles, nerves, and blood vessels are exposed to less trauma and clinically less postoperative pain is provided (13)(14)(15). This study was conducted to compare the postoperative analgesic efficacy of single-injection TPVB and ESPB in uniportal VATS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a single injection of an RLB was found to provide analgesia lasting only 2–3 h after breast surgery, which is a much shorter period than that reported for the PVB [ 39 ]. Additionally, in thoracoscopic surgery, PVBs provide better analgesia and result in less nausea than RLBs [ 28 ].…”
Section: Retrolaminar Blockmentioning
confidence: 99%
“…Moreover, contra-indications to thoracic epidural analgesia do not preclude PVBs in most cases. For thoracic surgeries, such as thoracotomies, PVBs provide better postoperative analgesia and lower opioid consumption than ESP blocks and RLBs [26][27][28]. Although conflicting results have been reported for breast cancer surgery [29], the analgesic efficacy of PVBs was found to be superior to that of ESP and other truncal blocks [7].…”
Section: Clinical Evidencementioning
confidence: 99%